Designing Business Strategy Formulation and Implementation: A Study on Geprek Neng Eyi in Subang Regency - Mutqi Sopiawadi; Alis Arifah Nurmala; Anadyas Putri Mulya Wijaya; Dea Agustina (Jurnal Pengabdian Masyarakat Al-Fatimah, 2025)
This study aims to design the formulation and implementation of business strategies at Ayam Geprek Neng Eyi in Subang Regency. The method used is a descriptive qualitative approach through SWOT analysis, as well as IFAS and EFAS matrices to evaluate the company's internal and external conditions. Data were obtained through observation, interviews with managers, and supporting documentation. The results showed that Ayam Geprek Neng Eyi has competitive advantages in the form of consistency of taste, strategic location, and affordable prices, although there are weaknesses such as limited parking and lack of social media management. Opportunities from population growth and people's preference for local flavors can be maximized through digital promotions. Meanwhile, threats in the form of intense competition and fluctuating raw material prices need to be addressed with innovative strategies. Implementation of the business strategy is focused on strengthening digital promotion, improving service quality, and developing human resources. The program is supported by a budget directed at improving production, operational, and marketing efficiency. With a systematic approach, Ayam Geprek Neng Eyi is expected to achieve the vision of becoming a leading restaurant that reaches more customers through the franchise model